Structural relationships among student teachers’ roles-strategies in promoting autonomous language learning - Nur Hidayanto Pancoro Setyo Putro; Yeni Fitri; Heri Retnawati; Yasir Alsamiri (Universitas Pendidikan Indonesia, 2022)
Evidence suggests that autonomous language learning has been one of the primary areas of interest in the field of English Language Teaching due to its fundamental roles in empowering students in taking the responsibility for their learning both in and out of the classroom. This study set out to investigate the structural relationships among the dimensions of English student teacher perception towards their roles and strategies in promoting autonomous language learning and professional autonomy. A total of 357 student teachers of English from Indonesia participated in this study. Eligibility criteria required the participants to have taken courses on English Language Teaching Methodology to ensure their understanding about the concepts of autonomous language learning and their future roles and strategies in fostering and promoting autonomous language learning. Structural Equation Modelling (SEM) with MPlus 7.2 was used to test the models proposed in this study. The findings showed that the dimensions of student teacher roles and strategies in promoting autonomous language learning and professional autonomy were weakly to moderately related to one another, suggesting how teacher education institutions need to provide sufficient trainings on the concept and practice of autonomous language learning. Several noteworthy findings are summarized and discussed thoroughly in the discussion section.